CORAL REEF RESISTANCE AND RESILIENCE: A CONSERVATION GENETIC PERSPECTIVE IN SUPPORTING CORAL REEF CONSERVATION PROJECT - Tyas Ismi Trialfhianty (Jurnal Pelita Teknologi, 2018)
A coral reef ecosystem is home to thousands of marine species and is utilised for feeding, reproduction and as a nursery ground. Coral reefs are areas of high biodiversity, and typically fish diversity and density are positively correlated with a living coral cover. Hence any threat to the coral ecosystem is also likely to have an impact on a high number of other species and may alter an environmental landscape. For instance, the decline of the coral population may reduce fish’s abundance and increase shoreline erosion. Contributions to the decline of coral reefs ecosystem from physical, chemical and biological sources such as increasing water temperatures (due to climate change), pollution, human disturbance and coral diseases. Therefore, it is important to understand factors which are related to the resistance and resilience of coral reef ecosystem. This review aims to broaden our understanding of coral reef resistance and resilience in the Indo-Pacific region by taking a genetic perspective. There are four primary aspects that are essential for coral resistance and resilience which will be reviewed here; the ability to respond to disturbance, the ability to adapt to the changing climate, the connectivity between coral populations (linked to larval dispersal), and the application of genetics to support coral reef conservation and management project. This paper is important to support our understanding of coral’s adaptability and resistance in facing disturbances such as climate change. Furthermore, it may benefit future conservation projects, as it explains genetic attributes that need to be considered for conservation and management projects such as local genetic diversity. Keywords: coral reef, conservation, genetic and population